Job Creation Tax Credits, Fiscal Foresight, and Job Growth: Evidence from U.S. States - Robert S. Chirinko; Daniel J. Wilson (Center for Economic Studies and ifo Institute (CESifo), 2016)
This paper studies the effects of job creation tax credits (JCTCs) enacted by U.S. states between 1990 and 2007 to gain insights about fiscal foresight (alterations of current behavior by forwardlooking agents in anticipation of future policy changes). Nearly half of the states adopted JCTCs during this period, and their experiences provide a rich source of information for assessing the quantitative importance of fiscal foresight. We investigate whether JCTCs affect employment growth before, at, and after the time they go into effect. A theoretical model identifies three key conditions necessary for fiscal foresight, captures the effects of the rolling base feature of JCTCs, and generates several empirical predictions.We evaluate these predictions in a difference-in-difference regression framework applied to monthly panel data on employment, the JCTC effective and legislative dates, and various controls. Failing to account for the distorting effects of fiscal foresight can result in upwardly biased estimates of the impact of the JCTC fiscal policy by as much as 33%. We also find that the cumulative effect of the JCTCs is positive, but it takes several years for the full effect to be realized. The cost per job created is approximately 16,000, which is low relative to cost estimates of recent federal fiscal programs.
Keywords: E62; E24; H25; H71; 330; fiscal foresight; job creation tax credits; state business tax incentives; implementation lags; fiscal policy